Avaliação da expressão de BPIF2A em pacientes que fizeram uso de bisfosfonato - Araujo, Quitéria Edileuza Rezende de (2019)
Bisphosphonates are medications often given to patients with bone tumor metastases and in patients with osteoporosis. One of the complications is osteonecrosis of the jaws. The use of saliva has been widely used in the diagnosis of some lesions. The objective of this study was to evaluate the expression of BPIFA proteins in saliva of patients undergoing bisphosphonate therapy. Sixteen patients were selected prospectively who did not use bisphosphonate and had tumor lesion; 13 patients who used bisphosphonate without the presence of osteonecrosis and 7 patients who used bisphosphonates and presented osteonecrosis lesions. After collection of saliva without stimulation, western blotting was performed for the BPIFA antibody. A reduction in BPIFA expression was observed in patients who used bisphosphonate and presented osteonecrosis of the jaw. Further studies are needed to better understand the pathogenesis of bisphosphonate osteonecrosis and BPIFA2 expression.